A study to assess the association of maternal factors and the outcome of pregnancy among mothers delivering in a tertiary care hospital in Haryana, India - Saini, Shveta; Singh, Mukhmohit; Mittal, Anshu (International Journal Of Community Medicine And Public Health, 2016)
Background: Low birth weight is a major cause of infant mortality and is considered as a sensitive index of the nation’s health and development. World Health Organization (WHO) defines low birth weight (LBW) as weight at birth of less than 2,500 grams (up to and including 2499 grams) irrespective of the gestational age. LBW is the leading cause of neonatal and postnatal deaths and as such it remains a worldwide issue and one of the most important public health problems, particularly in developing countries. The objectives of the study were to study the outcome of pregnancy whether normal, low birth weight, or still-birth, and to study the association of maternal risk factors- haemoglobin level, diabetes mellitus, hypertension and outcome of pregnancy. Methods: It was a cross sectional study carried out among the pregnant females delivering in MM Institute of Medical Sciences and Research, Mullana, Haryana, India from January 2010 to December 2010. A total of 500 cases were interviewed for the study purpose by systematic random sampling, using a semi structured pretested questionnaire. Data was analyzed using SPSS17 software. Results: Outcomes of pregnancy recorded were 28.8% low birth weight, 5.4% stillbirth and 65.8% normal birth weight. The mean birth weight was recorded as 2.556±0.411kgs. The incidence of LBW was maximum (54.3%) among the mothers who did not seek ANC while it was minimum (12.7%) in the ones who had sought ANC for more than 3 times. 57.6% mothers were anaemic and severe anaemia in 1.4% contributed towards more number of stillbirths and LBW infants (57.14% and 42.86% respectively). 4.2% mothers were found to be suffering from pregnancy induced hypertension (PIH). 69.41% of the mothers with any infection had delivered a low birth weight baby and 4.70% had a stillborn baby. Conclusions: The present study confirms birth weight as an important determinant of neonatal and post-neonatal outcomes.